2016
DOI: 10.1080/15548627.2016.1145325
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal putative RNA transporter SIDT2 mediates direct uptake of RNA by lysosomes

Abstract: Lysosomes are thought to be the major intracellular compartment for the degradation of macromolecules. We recently identified a novel type of autophagy, RNautophagy, where RNA is directly taken up by lysosomes in an ATP-dependent manner and degraded. However, the mechanism of RNA translocation across the lysosomal membrane and the physiological role of RNautophagy remain unclear. In the present study, we performed gain- and loss-of-function studies with isolated lysosomes, and found that SIDT2 (SID1 transmembr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
87
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(102 citation statements)
references
References 36 publications
4
87
0
Order By: Relevance
“…The primary and secondary antibodies used are: polyclonal goat anti-SIDT2 (N-20; Santa Cruz Biotechnology, sc-19991) to detect murine SIDT2, monoclonal rabbit anti-SCARB2/LIMP2 (EPR12080; Abcam, ab176317), horseradish peroxidase-conjugated anti-goat IgG (Jackson ImmunoResearch, 305-036-003) and horseradish peroxidase-conjugated anti-rabbit IgG (Thermo Scientific, 31460). The rabbit polyclonal anti-SIDT2 antibody used to detect human SIDT2 was prepared as described previously 9 . The Can Get Signal Immunoreaction Enhancer Solution (Toyobo, NKB101) was used for blots against murine SIDT2.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The primary and secondary antibodies used are: polyclonal goat anti-SIDT2 (N-20; Santa Cruz Biotechnology, sc-19991) to detect murine SIDT2, monoclonal rabbit anti-SCARB2/LIMP2 (EPR12080; Abcam, ab176317), horseradish peroxidase-conjugated anti-goat IgG (Jackson ImmunoResearch, 305-036-003) and horseradish peroxidase-conjugated anti-rabbit IgG (Thermo Scientific, 31460). The rabbit polyclonal anti-SIDT2 antibody used to detect human SIDT2 was prepared as described previously 9 . The Can Get Signal Immunoreaction Enhancer Solution (Toyobo, NKB101) was used for blots against murine SIDT2.…”
Section: Methodsmentioning
confidence: 99%
“…We have reported that constitutive degradation of cellular RNA is one of the physiological functions of RNautophagy 9 . Currently, the physiological roles of DNautophagy are unclear and warrant further examination.…”
mentioning
confidence: 95%
See 3 more Smart Citations